Pendampingan dan Pembuatan Anggaran Dasar (AD) dan Anggaran Rumah Tangga (ART), serta Rencana Anggaran Biaya (RAB) BUMDES Bunipah Kecamatan Aluh-Aluh - Rahma Yuliani; Kasyful Anwar; Ayu Oktaviani; Sofina Azkia; Muhammad Yasin; Atma Hayat (Universitas Lambung Mangkurat, 2023)
The change of management and management of BUMDES Bunipah Berkah Bersama caused a lack of knowledge of BUMDES managers in preparing and making AD, ART, and RAB. This community service activity aims to provide assistance so that BUMDES managers understand the formulation and preparation of AD, ART, and RAB and BUMDES has the necessary cost budget design. This activity was carried out using a mentoring method given to the manager of BUMDES Bunipah Berkah Bersama. The output of this activity is that the manager understands the basic legal basis, organizational guidelines contained in the AD and ART, understands making a good and correct RAB so that village funds can be maximally utilized and the formation of AD, ART, and RAB documents.